2021
DOI: 10.31603/nursing.v8i2.4808
|View full text |Cite
|
Sign up to set email alerts
|

The demands on nursing curriculum flexibility towards the need of global workforce: A systematic review

Abstract: The demand for Indonesian nurses to work abroad has increased over the last five years. The challenge is that the orientation of the nursing education curriculum in Indonesia is still local, not yet leading to international standards. As a result, only a small number of nurses passed the selection, the process is longer, and the recruitment cost is higher. Therefore, this review aims to identify the global need for Indonesian nurses and provide an overview of the importance of structured planning in terms of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Empowerment in the health sector entails incorporating them into the training of abroad nurses, entrepreneurs, independent nurse clinics, and medical tourism (Hardy, Hadi, & Tukayo, 2021). Those industries have never been without a requirement for nurses (Al-Ashwal et al, 2020;Hardy, Hadi, & Tukayo, 2021;Zulfikar, 2016). In this step, we planned what we would do differently in similar or related situations in the future.…”
Section: Diagram 1 Reflective Cycle Gibbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowerment in the health sector entails incorporating them into the training of abroad nurses, entrepreneurs, independent nurse clinics, and medical tourism (Hardy, Hadi, & Tukayo, 2021). Those industries have never been without a requirement for nurses (Al-Ashwal et al, 2020;Hardy, Hadi, & Tukayo, 2021;Zulfikar, 2016). In this step, we planned what we would do differently in similar or related situations in the future.…”
Section: Diagram 1 Reflective Cycle Gibbsmentioning
confidence: 99%
“…The proposal should explain the plan and objectives of the activity clearly and in detail that requires the approval of other parties. As suggested by many research finding, to create proposals for this issue, we suggested organizing a small pilot project committee comprised of government representatives, manpower agents, community representatives, professional groups, university representatives, and ex-migrant nurses (Hardy, Hadi, & Tukayo, 2021;Philip et al, 2018). According to various research findings, the objective of the proposal is to discover exceedingly essential challenges and solutions associated with the empowerment of ex-migrant nurses by concerning all available potentials, incorporating supportive and inhibiting variables (Efendi et al, 2015;Espino-Díaz et al, 2020).…”
Section: Diagram 1 Reflective Cycle Gibbsmentioning
confidence: 99%
“…The complexity of the midwifery education program includes the vocational education program, which in Indonesia recognizes the diploma III program (Hill & Fitzgerald, 2020). A vocational program of this type is the most popular midwifery education program in Indonesia (Hardy et al, 2021). Therefore, graduates of vocational midwifery education are widely spread.…”
Section: Introductionmentioning
confidence: 99%
“…The number of migrant workers abroad is around 3 million workers but the membership has only reached 400,000 workers (BP Jamsostek, 2020). Among them are nurses who are the top most Indonesian healthcare workers abroad (Hardy et al, 2021). According to the labor law, they deserve welfare and protection particularly during the Covid-19 pandemic (Djatmiko, A., & Pudyastiwi, 2019;ILO, 2020;TNP2K, 2018).…”
Section: Introductionmentioning
confidence: 99%